Using The Roll Play Method to Improve Student's English Speaking Skills: English - Adip Efendi efendi (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2023)
This study conducted to develop students’ speaking skills.In this study, the researcher used a classroom action research (CAR) method using a Kurt Lewin design which consisted of planning, acting, observing, and reflecting. it used two cycles where each cycle consists of two meetings. The application of role play in the classroom was very popular with students, this was based on the results of the questionnaire85,99% into very strong categories. In addition, students also experienced a significant increase from before the application of role play, this was proven by the results of the students' scores during classroom action research, namely pre-test 61.58, post-test 1 73.32, post-test 2 79.22. These results indicate that the role-play method can be used as a medium of learning to improve student's English skills.